Cosmopolitans and Heretics: New Muslim Intellectuals and the Study of Islam By Carool Kersten (New York: Columbia University Press, 2011. 288 pages.) (American Journal of Islam and Society, 2012)
It is a rare treat to find an English-language work of intellectual history by ascholar who is proficient in Arabic, Indonesian, and French – and thus capableof bringing together the Indonesian Islamicist Nurcholish Madjid (1939-2005), the Egyptian philosopher Hasan Hanafi (1935-), and the French-Algerian Islamicist Mohamed Arkoun (1928-2010). Carool Kersten offersthe first systematic treatment in English of these three figures’ thought andconvincing arguments for why they not only deserve consideration together,but also why, when taken together, they represent a significant developmentin Islamic thought.Kersten argues that these three Islamic thinkers form part of “the first generationof Muslim thinkers reaching intellectual maturity in the postcolonialage” and are “representative of a new type of Muslim intellectual emergingin the 1960s” (p. xiv). Despite the enthusiastic language he associates withthese “pioneers” and “trailblazers” (p. xvi), the author wisely takes care todraw attention to what these figures owe to earlier scholars and thinkers atmany points. He also avoids overstated claims about how they either exemplifyor hold great influence over their generation as a whole ...